IMPLEMENTING VALUE STREAM MAPPING (VSM) ON PRODUCTION PROCESS OF BLANK CYLINDER HEAD AT PT X - Hartono, Gunawarman; Prajadhiana, Dendi; Nurhidayat, Syarif (Industrial and Systems Engineering Assessment Journal (INASEA), 2009)
In order to achieve competitive advantage and sound business processes, one of the strategies developed is aimed at production process efficiency by eliminating all types of waste within the process.. Value Stream Mapping (VSM) method is utilized to detect the sources of such wastes. This research is intended to yield the value added to each of the working elements as well as those working elements that do not give significant product value. The added value is then accumulated by using certain formula to come up with Process Cycle Efficiency (PCE). The PCE figure indicates how well the company performs in terms of its process efficiency. Once this PCE figure is obtained, the sources of inefficiency can then be detailed by constructing VSM sheet and charting the Current State Value Stream Mapping. It can then be clearly identified where the actual efficiency problems lie within the production process. This VSM research can be used by the company as a tool to improve efficiency-related problems to obtain more efficient and effective production process.